Counselling in schools - Bor, Robert (SAGE, 2002)
This text is a practical, contemporary guide to providing effective counselling support within school settings. It is an invaluable resource for anyone wishing to provide counselling support for pupils in secondary education.
Keywords: Counseling in secondary education -- Great Britain.; Educational counseling -- Great Britain.; Counseling in secondary education.; Educational counseling.; Services personnels aux élèves du secondaire.; Orientation scolaire.; Services personnels aux élèves du secondaire -- Grande-Bretagne.; EDUCATION -- Counseling -- General.; Counseling in secondary education; Educational counseling; Great Britain; Conseiller d'orientation.; Enseignement secondaire.; Pratique professionnelle.; Royaume-Uni.; Guide (Descripteur de forme)